Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Stres Pasien TB Paru pada Masa Pandemi Covid-19 - Bioladwiko, Bioladwiko; Azam, Mahalul; Rahayu, Sri Ratna (Universitas Negeri Semarang, 2022)
Stress is an unexpected reaction that arises as a result of the high demands of the environment on a person. Covid-19 causes fear and stress. Stress events also occur in pulmonary TB patients which are manifested physically, psychologically, and behaviorally due to the conditions they are experiencing.analyze Factors related to the incidence of stress in pulmonary TB patients during the Covid-19 pandemic.This research is an analytical survey research with a cross sectional approach. The population of this study were pulmonary TB patients at level II health facilities, namely Pantiwilasa General Hospital dr. Cipto which is a health facility with high category pulmonary TB patients as many as 204 patients.The sample that was successfully obtained as a whole was 189 respondents, The sampling technique used is total sampling. The research instrument used is a questionnaire. The data analysis in this study were univariate analysis (frequency distribution), bivariate analysis (rank Spearman correlation test) and multivariate analysis (ordinal logistic regression test). The results showed that there was a significant relationship between age, gender, knowledge, socio-culture and environment with the incidence of stress in pulmonary TB patients during the Covid-19 pandemic. Education, work and sources of information are not factors related to the incidence of stress in pulmonary TB patients during the Covid-19 pandemic. Gender, environment and age are the factors with the strongest relationshipwiththe incidence of stress in pulmonary TB patients during the Covid-19 pandemic.